Soviet women in combat : a history of violence on the Eastern Front - Krylova, Anna. (Cambridge ; New York : Cambridge University Press, 2011)
"Soviet Women in Combat explores the unprecedented historical phenomenon of Soviet young women's en masse volunteering for World War II combat in 1941 and writes it into the twentieth-century history of women, war, and violence. The book narrates a story about a cohort of Soviet young women who came to think about themselves as women soldiers in Stalinist Russia in the 1930s and who shared modern combat, its machines, and commanding positions with men on the Eastern front between 1941 and 1945. The author asks how a largely patriarchal society with traditional gender values such as Stalinist Russia in the 1930s managed to merge notions of violence and womanhood into a first conceivable and then realizable agenda for the cohort of young female volunteers and for its armed forces. In pursuing this question, Anna Krylova's approach and research reveals a more complex conception of gender identities."--Page [i] of text.
A portrait of a young woman as the citizen soldier -- "And this is exactly who we are--soldiers!" : women volunteers, local authorities, and the Stalinist government in 1941 -- The exceptional mobilization of 1941 : the making of a female combat collective by state order -- New gender landscapes for the Army : from grassroots enlistments to the state-run mobilizations of 1942-45 -- Partners in violence : the woman soldier and the machine in the 1941 trenches -- "To be a woman commander--that was great!" : remechanizing and regendering in the Red Army, 1942-45 -- Bonded by combat : women and men sharing violence, authority, and romance in mechanized warfare, 1942-45.
Includes bibliographical references (pages 303-313) and index.
Keywords: Soviet Union. -- x; Soviet Union. -- 2; 1939-1945; World War, 1939-1945 -- Soviet Union; World War, 1939-1945 -- Participation, Female; World War, 1939-1945 -- Campaigns -- Eastern Front; Women soldiers -- Soviet Union -- History; Women and war -- Soviet Union -- History; Women and the military -- Soviet Union -- History; Sex role -- Soviet Union -- History; Military campaigns; Military participation -- Female; Sex role; Women and the military; Women and war; Women soldiers; Eastern Front (World War (1939-1945)); Soviet Union; History